2015
DOI: 10.1111/josi.12127
|View full text |Cite
|
Sign up to set email alerts
|

How Does Intergroup Contact Affect Social Change? Its Impact on Collective Action and Individual Mobility Intentions among Members of a Disadvantaged Group

Abstract: A current debate surrounds the issue of whether prejudice‐reducing interventions such as intergroup contact may reduce resistance to unequal intergroup relations among disadvantaged groups. Addressing this question, this research investigates how positive contact with members of the advantaged group shapes action strategies to cope with disadvantage. Using survey data from a sample of Latino Americans (N = 112), structural equation modeling revealed that friendship contact with Anglo‐Whites was overall negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 34 publications
6
107
1
1
Order By: Relevance
“…The extent to which participants identified with people of the same sexual orientation (e.g., bisexual people), transgender people, and/or the LGBT+ movement was measured using Leach et al's (2008) three-item solidarity and centrality subscales. Anger was measured as the extent (1 = not at all, 5 = extremely) to which respondents felt angry, resentful, furious, and displeased about the discrimination against LGB+ and/or transgender people (Tausch, Saguy, & Bryson, 2015). Outgroup attitudes were assessed with a feeling thermometer (Converse et al, 1980).…”
Section: Measures For Lgbt+ Respondentsmentioning
confidence: 99%
“…The extent to which participants identified with people of the same sexual orientation (e.g., bisexual people), transgender people, and/or the LGBT+ movement was measured using Leach et al's (2008) three-item solidarity and centrality subscales. Anger was measured as the extent (1 = not at all, 5 = extremely) to which respondents felt angry, resentful, furious, and displeased about the discrimination against LGB+ and/or transgender people (Tausch, Saguy, & Bryson, 2015). Outgroup attitudes were assessed with a feeling thermometer (Converse et al, 1980).…”
Section: Measures For Lgbt+ Respondentsmentioning
confidence: 99%
“…Consistent with the literature on collective action, it may be conflict (vs. peace) that is necessary for collective action (Wright & Baray, ; Wright & Lubensky, ). While promoting positive intergroup attitudes, intergroup contact can enhance (inaccurate) expectations that the disadvantaged group will be treated fairly by the advantaged group (Saguy et al, ), promote a common ingroup identity (Gaertner & Dovidio, ) reduce anger toward the outgroup (Tausch, Saguay, & Bryson, ) and reduce perceptions of discrimination (Dixon, Tropp et al, ). All of these outcomes can reduce perceptions of group inequality and hence reduce motivation to challenge group inequality (Dixon et al, ; Saguy et al, ; Ufkes, Calcagno, Glasford & Dovidio, ; Ufkes, Dovidio & Tel, ; van Zomeren, Postmes, & Spears, ).…”
Section: The Mixed Outcomes Of Intergroup Contact: Why Does This Paramentioning
confidence: 99%
“…Crucial to the present study, the sedating effect of positive intergroup contact was mediated by reduced ethnic identification. Tausch et al (2015) found a similar disidentification process among Latino-American students resulting from present interethnic friendships with Whites. In the current study, we thus also expect that positive intergroup contact with the Bulgarian national majority is related to reduced ethnic activism among the Bulgarian Roma minority through diminished ethnic identification.…”
Section: Introductionmentioning
confidence: 67%
“…Outgroup derogation (e.g., prejudice) is one strategy. Individual upward mobility from a discriminated group to another more privileged one is another (see Tausch et al, 2015). Furthermore, recent studies on negative identity management have proposed that disadvantaged ethnic minority members cope by “navigating” multiple group identities (e.g., Curtin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%